2014
DOI: 10.1186/1471-2164-15-799
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the gene expression profiles of the brains of male European eels (Anguilla anguilla) during sexual maturation

Abstract: BackgroundThe vertebrate brain plays a critical role in the regulation of sexual maturation and reproduction by integrating environmental information with developmental and endocrine status. The European eel Anguilla anguilla is an important species in which to better understand the neuroendocrine factors that control reproduction because it is an endangered species, has a complex life cycle that includes two extreme long distance migrations with both freshwater and seawater stages and because it occupies a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…The role of tac in influencing sexual behaviors in teleosts has not been addressed, but tac expression significantly increases in the brain of male eels ( Anguilla anguilla ) during sexual maturation [95] and leads to increased male aggression in Drosophila [90]. In bluegill, the primary role of tac expression may not be male-male aggression, considering higher expression levels of this gene are also observed in the non-aggressive satellite and sneaker males when compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…The role of tac in influencing sexual behaviors in teleosts has not been addressed, but tac expression significantly increases in the brain of male eels ( Anguilla anguilla ) during sexual maturation [95] and leads to increased male aggression in Drosophila [90]. In bluegill, the primary role of tac expression may not be male-male aggression, considering higher expression levels of this gene are also observed in the non-aggressive satellite and sneaker males when compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…In general, immune competency is depressed by activation of HPA (reviewed in Norris and Hobbs, 2006) and the down-regulation of immune system genes is associated with increased stress at reproduction. In our previous study, we found that genes involved in immune system function were down-regulated in the brains of eels at sexual maturity (Churcher et al, 2014). Furthermore, previous work in other fish has shown that treatment with 17-β estradiol resulted in a decrease in the expression of immune related transcripts (Tilton et al, 2006;Williams et al, 2007).…”
Section: Tablementioning
confidence: 96%
“…A false discovery rate of 5% was used and only genes with a minimum fold change of 1.5 were considered. The array and methods used in this study have previously been verified using qPCR and a subset of eight genes in Churcher et al (2014).…”
Section: Sample Preparation and Microarray Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most notable results from the transcriptomic data from all the tissues were the enrichment of GO terms related to the immune response in the brain and have been hypothesized to be part of the adaptation of eels in preparation for migration (Pankhurst and Lythgoe 1983). Furthermore, the upregulation of genes involved in photo signal transduction and visual system development (Churcher et al 2014), and alterations to the retina, have previously been observed in developing European eels (Pankhurst and Lythgoe 1983).…”
Section: Differential Brain and Pituitary Gene Expressionmentioning
confidence: 84%